Letter (copy) : Spain - Tewson, Vincent
012b-0056-001 International. HVT/EAB/AT/497. 31st January, 1939. M. Leon Jouhaux, Confederation Generale du Travail, 211 rue Lafayette, Paris. Dear Comrade Jouhaux, SPAIN I have your letter of the 28th instant and thank you very much for keeping us informed of the action which your Executive have taken with a view to assisting our Spanish comrades in their fight against the Fascist invaders. With best wishes, Yours sincerely, Assistant Secretary. 292/946/12b/56